2016
DOI: 10.17582/journal.sja/2016.32.4.325.333
|View full text |Cite
|
Sign up to set email alerts
|

Improved Soil Physical Properties, Yield and Water Productivity under Controlled Traffic, Raised-Bed Farming

Abstract: Excessive irrigation application and intensive tillage is the norm on Pakistani farms, which exacerbate water logging and salinity and reduce the water productivity of major crops. Addressing these issues, a long term experiment (2000 to 2009) under wheat-maize (9 seasons each) cropping pattern was conducted on raised beds (with furrow spacing of 65 cm (Narrow Bed-NB), 130 cm (Medium Bed-MB) and 180 cm (Wide Bed-WB)), with controlled traffic regime emplaced, in comparison with traditional intensive cultivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The chemical properties of this soil were improved by using this practice, which the soil salinity reduced more than 50% approximately, especially for Cland Na + in the root zone of maize under raised bed system, led to increase of availability nutrients to crops and nutritional balances. Akbar et al (2016) showed the prospects of improved soil physical properties and water productivity by adopting controlled traffic raised bed farming (CTRBF) system, which may be helpful for agriculture sustainability and food security. Recently, EL Azab and Mahmoud (2017) indicated that the raised bed system application is the candidate strategy for reduction of salt stress in root zone at a newly reclaimed soil, which the faba bean plants were able to complete its life cycle despite high soil salinity, as consequence to realize good manage for salt accumulation under raised bed condition.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical properties of this soil were improved by using this practice, which the soil salinity reduced more than 50% approximately, especially for Cland Na + in the root zone of maize under raised bed system, led to increase of availability nutrients to crops and nutritional balances. Akbar et al (2016) showed the prospects of improved soil physical properties and water productivity by adopting controlled traffic raised bed farming (CTRBF) system, which may be helpful for agriculture sustainability and food security. Recently, EL Azab and Mahmoud (2017) indicated that the raised bed system application is the candidate strategy for reduction of salt stress in root zone at a newly reclaimed soil, which the faba bean plants were able to complete its life cycle despite high soil salinity, as consequence to realize good manage for salt accumulation under raised bed condition.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the potential yield of basmati rice in Pakistan is 5.2 t ha‾¹, but the present national yield is approximately 1.6 t ha‾¹; thus, there is a yield gap of 3.6 t ha‾¹ (Aslam et al, 2002). The reasons for the low yield are generally attributed to the availability issues of site-specific high-yielding rice varieties, input mismanagement, low soil fertility and inappropriate field management practices (Akbar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, during the autumn-winter cycle, the availability of water depends almost exclusively on irrigation. Under these conditions, there is less infiltration and availability of water in wide beds, because the center of the bed is not wetted completely due to a lower lateral flow and the lower amount of water applied, so the crop rows in the center of the bed do not receive the required amount of water [2,28,30]. This could explain the trend towards lower yield of wheat on wide permanent beds in Irapuato I and Pénjamo.…”
Section: Discussionmentioning
confidence: 99%